ANALISIS PRODUKTIVITAS KERJA PEGAWAI BALAI LATIHAN KERJA (BLK) PADANG - Liza Zulbahri (Ensiklopedia Social Review, 2021)
The purpose of this study was to determine the effect of work discipline and communication on work productivity of the Padang Job Training Center (BLK) employees. The research method used is descriptive quantitative. The sampling technique used is saturated sampling, so that from the population there are 59 respondents, the data collection methods used are observation, questionnaires, and literature study. The data analysis technique used is multiple linear regression, t test, F test and coefficient of determination. Based on multiple linear regression analysis, the variables of work discipline and communication on work productivity of the Padang Job Training Center (BLK) employees obtained Y = 6.747 + 0.931 X1 + 0.178 X2 + e. The results of the t-test that were carried out showed that the variables of work discipline and communication had a significant effect on the work productivity of the Padang Job Training Center (BLK) employees. The results of the F test proved that the variables of work discipline and communication had a positive and significant effect simultaneously on the work productivity of the Padang Job Training Center (BLK) employees. This can be proven by the value of Fcount > Ftable or 534,421 > 3.16 and a significant level of 0.000 Alpha (α) 0.05 while the coefficient of determination is 94.8%. (BLK) Padang, while the remaining 5.2% is explained by other variables not examined in this study.